Ineffectiveness of Lactobacillus johnsonii LA1 for prophylaxis of postoperative recurrence in Crohn's disease: a randomised, double blind, placebo controlled GETAID trial. Issue 6 (23rd December 2005) - Marteau, P; Lémann, M; Seksik, P; Laharie, D; Colombel, J F; Bouhnik, Y; Cadiot, G; Soulé, J C; Bourreille, A; Metman, E; Lerebours, E; Carbonnel, F; et al.
Abstract : Background and aims: Early endoscopic recurrence is frequent after intestinal resection for Crohn's disease. Bacteria are involved, and probiotics may modulate immune responses to the intestinal flora. Here we tested the probiotic strain Lactobacillus johnsonii LA1 in this setting. Patients and methods: This was a randomised, double blind, placebo controlled study. Patients were eligible if they had undergone surgical resection of <1 m, removing all macroscopic lesions within the past 21 days. Patients were randomised to receive two packets per day of lyophilised LA1 (2×10 9 cfu) or placebo for six months; no other treatment was allowed. The primary endpoint was endoscopic recurrence at six months, with grade >1 in Rutgeerts' classification or an adapted classification for colonic lesions. Endoscopic score was the maximal grade of ileal and colonic lesions. Analyses were performed primarily on an intent to treat basis. Results: Ninety eight patients were enrolled (48 in the LA1 group). At six months, endoscopic recurrence was observed in 30/47 patients (64%) in the placebo group and in 21/43 (49%) in the LA1 group (p = 0.15). Per protocol analysis confirmed this result. Endoscopic score distribution did not differ significantly between the LA1 and placebo groups. There were four clinical recurrences in the LA1 group and three in the placebo group. Conclusion: L johnsonii LA1 (4×10 9 cfu/day) did not have a sufficient effect, if any, to prevent endoscopic recurrence of Crohn's disease.